Cairns Zoning Plan Review: Issues - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 1988)
The Great Barrier Reef is the largest and richest system of coral reefs in the world. Recognised as one of the world's great natural heritage areas, it has been described on the World Heritage List, and conserved for future generations through legislation.
Keywords: Great Barrier Reef (Qld.); Marine parks and reserves; Great Barrier Reef Marine Park Cairns section; Zoning; Management; Planning; Tourism; Environmental management; Mapping; Legislative tools; Zones, plans and maps; Managing Multiple Use; Cairns/Cooktown Management Area